The english legal system - Martin, Jacqueline (Hodder education, London, 2013)
"The English Legal System" by Jacqueline Martin is highly regarded as an accessible and comprehensive introduction to the intricacies of the English legal system. Here are some key points often highlighted in reviews: Clarity and Accessibility: Readers appreciate Jacqueline Martin's ability to explain complex legal concepts in a clear and understandable manner, making the book suitable for both law students and those with a general interest in the subject. Comprehensive Coverage: The book covers all essential aspects of the English legal system, including the judiciary, sources of law, court procedures, and the role of key legal institutions. Updated Information: Martin's book is frequently updated to reflect changes in the legal landscape, ensuring that readers have access to current and relevant information. Useful Learning Features: The book includes helpful learning features such as case studies, diagrams, and summaries that aid in understanding and retention of the material. Practical Relevance: Many readers find the practical examples and real-life applications provided in the book to be particularly valuable in understanding how the legal system operates in practice. Overall, "The English Legal System" by Jacqueline Martin is often recommended for its clarity, comprehensiveness, and practical approach to understanding the workings of the English legal system.
"The English Legal System" by Jacqueline Martin offers a clear and comprehensive introduction to the structure and functioning of the legal system in England and Wales. It covers essential topics such as the judiciary, sources of law, court procedures, and the role of key legal institutions. The book is praised for its accessibility, practical examples, and regular updates to reflect current legal developments, making it an invaluable resource for students and anyone interested in understanding English law.
Keywords: Sources of law; Law in England and Wales